Reshaping Healthcare: A Bibliometric Analysis of Lessons Learned in Post-COVID-19 Health Policy - Azizan, Azliyana; Abdullah, Khairul Hafezad; Rahayu, Sri Ratna; Rusli, Nadia Safirah; Tarmidzi, Nornajehah (UI Scholars Hub, 2023)
The COVID-19 pandemic has profoundly impacted health policy globally, leading to heightened concern and urgency. However, previous studies have been hampered by limited resources and insufficient discussions on the long-term implications for health policies following multiple COVID-19 waves. Thus, this study examined the evolution of international studies on post-COVID-19 health policy. A comprehensive analysis used well-known literature databases Scopus and Web of Science to explore parameters including publication growth, participating countries, areas of interest, and keyword analysis of topics such as